Association between dietary protein intake and bone mineral density based on NHANES 2011–2018 - Xingxing Chen; Yonghua Fu; Zhongxin Zhu (Scientific Reports)
Abstract This study examines the relationship between dietary protein intake and bone mineral density (BMD) using data from the 2011–2018 National Health and Nutrition Examination Survey (NHANES), addressing existing controversies in current evidence. This cross-sectional study included 16,775 participants. Dietary protein intake, the exposure variable, was collected with the use of two 24-h dietary recall methods and usual intake was assessed by the National Cancer Institute (NCI) method. While whole-body BMD, the outcome variable, was measured with dual-energy X-ray absorptiometry. Covariates included demographic, socioeconomic, and health factors. Weighted multivariable regression and generalized additive models were used for the association between dietary protein intake and BMD. After adjusting for covariates, a positive association was found between protein intake and BMD. Each additional gram of protein consumed was significantly associated with a BMD increase of 0.0003 g/cm2 (95% CI 0.0001, 0.0004, P = 0.0003). Subgroup analysis by gender and ethnicity revealed significant positive correlations in women and Mexican Americans. Additionally, a saturation threshold effect was observed in women at 60.70 g/day and in non-Hispanic whites at 135.53 g/day, where the correlation was no longer significant beyond these thresholds. The study demonstrates a positive association between dietary protein intake and BMD, although this relationship is complex and nonlinear with varying effects across different populations. Specifically, positive correlation is only significant below a specific threshold level in some populations. These findings suggest the need for personalized dietary guidelines and provide important insights for clinical nutritional interventions and bone health management.